Artificial Intelligence-Driven Tactical Analysis In Football Training - DANG, XU (Pacific International Journal, 2025)
With the rapid development of artificial intelligence technology, the application of AI in competitive sports continues to deepen, reshaping the structure and logic of football training. Based on the literature method, this article selects 45 representative research results on topics such as "artificial intelligence", "football training", and "physical education" from Chinese core and English authoritative journals from 2002 to 2025 as analysis samples, and systematically sorts out the application paths and development trends of AI technology in modern football training. The study found that artificial intelligence is mainly used in key links such as motion recognition, tactical modeling, fatigue monitoring and injury prediction, which effectively improves the accuracy of training, the real-time feedback and the scientific nature of strategy adjustment. For example, through the fusion of computer vision and sensor data, real-time capture of players’ movement postures and deviation warnings can be achieved; with the help of machine learning models and spatial analysis algorithms, decision-making efficiency in tactical drills can be significantly improved. In the educational dimension, the introduction of AI has broken the barriers between theoretical teaching and practical training, and promoted the transformation of college sports courses to "data-driven" and "technology-enabled". The study further pointed out that colleges and universities should strengthen students’ data literacy, platform operation capabilities and interdisciplinary technology understanding in coach training to adapt to new teaching requirements in the context of intelligence. Combining actual teaching experience, the article constructs a multidimensional model of college football training under AI empowerment, and puts forward optimization suggestions at the education system level in terms of curriculum reform, technology introduction and teacher training. This study not only clarifies the technical context of the current integration of artificial intelligence and football training, but also provides a theoretical basis and practical path for the intelligent transformation of sports education, which has important practical significance and forward-looking value.